Development of Spiritual IPA Module on Environtment Pollution Subject for Junior High School - Rahma Sartika; Lufri Lufri (Universitas Negeri Padang, 2018)
The purposes of this research are to produce valid and practice nuanced spiritual module about Environment Pollution for class VII SMP/MTs. This study uses three stages of plomp models. The subjects of this study were 29 students of class VII SMP Negeri 25 Padang and 2 teachers. The object of this research is spirituality module IPA on the material of Environment Pollution in validated human validator 3. The data of this research are primary data collected from validity and questionnaire of data practicality. The result of validity is 86,63% with valid criterion, practicality by teacher and student practical with 82,46% value by teacher and 88,69% by student. Key words: Spiritual module, Environment Pollution